Extractive industries: enclaves or a means to transform economies? - Tony Addison; Alan Roe (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
This paper argues for a change in government attitudes to their extractive industries: as enclaves useful primarily as revenue sources. This is too narrow a perspective: it fails to recognize the broader economic linkages that are invariably possible. Achieving greater economic impact requires governments to redefine how best to encourage economic diversification. Specifically, manufacturing activities tend to be over-emphasized, especially those based on a narrow view of local content ignoring competitiveness, while opportunities in the renewable resource economy are underemphasized (especially agriculture, the livelihood of millions of poor people, and ecosystem services). Moreover, industrial policy will not succeed when policies and investments in energy, enterprise development (especially for small and medium-sized enterprises), and financial systems are neglected. Stronger development finance institutions can be key players-one lesson from Latin American successes. Sharing power and transport infrastructure can further strengthen further the linkages from extractive industries to local and national economies.
Keywords: L71; L72; Q18; N16; 330; agriculture; extractive industries; industrial policy; mining; natural gas; oil